1999
DOI: 10.1076/jcen.21.2.186.927
|View full text |Cite
|
Sign up to set email alerts
|

WISC-III Index Growth Curve Characteristics Following Traumatic Brain Injury

Abstract: Previous studies have replicated the four-factor structure of the WISC-III in children with traumatic brain injury (TBI) and demonstrated the sensitivity of WISC-III indexes to severity of injury. This archival study examined the growth curve characteristics of the indexes following traumatic brain injury. The primary hypothesis was that there is systematic variability in the components (e.g., slope) of the curves. Subjects included 40 children with documented loss of consciousness, age at injury 9.3 years (SD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
4
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 19 publications
2
4
0
Order By: Relevance
“…Many studies, including ours, consistently demonstrate a weakness in Processing Speed and Freedom from Distractibility relative to Verbal Comprehension and Perceptual Organization for children with ADHD, LD, and autism (Mayes et al, 1998a;Mayes, Calhoun, & Crowell, 1998b;Mayes & Calhoun, 2003a;Mealer et al, 1996;Naglieri et al, 2003;Newby et al, 1993;Nyden et al, 2001;Prifitera & Dersh, 1993;Saklofske et al, 1994;Schwean et al, 1993;Snow & Sapp, 2000;Wechsler, 1991). Consistent with our study, other research has shown that children with traumatic brain injury perform more poorly on Processing Speed and Perceptual Organization than on the verbal factors (Donders & Warschausky, 1997;Hoffman, Donders, & Thompson, 2000;Kay & Warschausky, 1999). For our study and all published clinical studies reporting subtest scores, Coding is lower than Symbol Search.…”
Section: Conclusion Regarding Profile Analysissupporting
confidence: 93%
“…Many studies, including ours, consistently demonstrate a weakness in Processing Speed and Freedom from Distractibility relative to Verbal Comprehension and Perceptual Organization for children with ADHD, LD, and autism (Mayes et al, 1998a;Mayes, Calhoun, & Crowell, 1998b;Mayes & Calhoun, 2003a;Mealer et al, 1996;Naglieri et al, 2003;Newby et al, 1993;Nyden et al, 2001;Prifitera & Dersh, 1993;Saklofske et al, 1994;Schwean et al, 1993;Snow & Sapp, 2000;Wechsler, 1991). Consistent with our study, other research has shown that children with traumatic brain injury perform more poorly on Processing Speed and Perceptual Organization than on the verbal factors (Donders & Warschausky, 1997;Hoffman, Donders, & Thompson, 2000;Kay & Warschausky, 1999). For our study and all published clinical studies reporting subtest scores, Coding is lower than Symbol Search.…”
Section: Conclusion Regarding Profile Analysissupporting
confidence: 93%
“…Although none of the comparisons of the RIAS and WISC scores were significant, some did exhibit expected patterns. For example, the RIAS NIX was 4.4 points higher than the WISC-III PIQ, which is expected because the PIQ includes subtests requiring visuomotor and processing speed, which have been shown to decline as a result of TBI (Bawden, Knights, & Winogron, 1985;Calhoun & Mayes, 2005;Donders, 1997;Kay & Warschausky, 1999;Thaler et al, 2010;Tremont, Mittenberg, & Miller, 1999). Although it was expected that the RIAS NIX would be significantly higher than the WISC-III POI because the POI has demonstrated some sensitivity to TBI in prior studies, the difference was negligible (1.3 points).…”
Section: Discussionmentioning
confidence: 69%
“…The initial attempt at this analysis included all four index scores: Verbal Comprehension (VC), Freedom From Distractibility (FD), PS, and PO. However, HLM did not resolve the equation in a reasonable number of iterations when the FD score was included in the analyses, similar to findings in a previous growth curve analysis study using WISC-III index scores (Kay & Warschausky, 1999). Therefore, FD was omitted from further analyses.…”
Section: Growth Curve Analysesmentioning
confidence: 88%